Analysis of the entrepreneurial process from effectuation and causation logic: a case study in two companies from Minas Gerais - Ferreira, Karina Fernanda Oliveira; Guimarães, Liliane de Oliveira; Salume, Paula Karina; Doyle, Maria Luiza de Fátima Costa Proença (Revista de Administração da UFSM, 2022)
Objective: The article aimed to analyze how the effectuation and causation logics were used in the entrepreneurial process of two companies from Minas Gerais. The effectuation logic is based on issues related to the entrepreneur’s decision making and contrasts with the causation logic - which refers to traditional methods of the entrepreneurial process based on planning and determined sequences. Methodology: A qualitative comparative study was carried out in two companies from Minas Gerais. The evidence was obtained from interviews with the founding partners, in addition to observation and documents, and the data analysis was performed using content analysis. Results: The results showed that in the two cases analyzed, the entrepreneurs relied on effectuation logic for setting up the businesses, with little use of causation logic but as the businesses consolidated and moved beyond the initial founding phase, the entrepreneurs took different attitudes, basing their decisions and actions on greater planning and systematic analysis of the context. Limitations: Some studies show that cultural differences can have an influence on the entrepreneurial process and how entrepreneurs make decisions. This variable was not contemplated in this study, which represents a limitation. Additionally, the study analyzed the entrepreneurial process of two companies from Minas Gerais, which does not allow for generalization. Originality/contributions: the work contributes to the national studies on the entrepreneurial process, mainly from the principles that compose the effectuation logic, seeking to identify and classify the decisions and actions of entrepreneurs in the causation and effectuation logics.